Pengaruh Independensi, Akuntabilitas dan Etika Auditor Terhadap Kualitas Auditor - Fauziah, Novita Wahyu; Sudaryanti, Dwiyani; Anwar, Siti Aminah (e_Jurnal Ilmiah Riset Akuntansi, 2023)
This study aims to determine the influence of independence, accountability and auditor ethics on auditor quality. The independent variables in this study are the independence, accountability and auditor ethics of the auditor quality, while the dependent variable is the quality of the auditor. This type of research is quantitative research, because the data that used in the form is numerical data. The source of this research data is primary data with the data collection method in the form of questionnaires. The population in this study is auditors who work in Public Accounting Firms in Malang city. The data retrieval technique uses the slovin formula. Based on this method, the number of auditors used was 100 respondents. Hypotheses tested using descriptive statistical analysis, instrument tests, normality tests, classical assumption tests, multiple linear regression tests and hypothesis tests using SPSS Version 22 tools. The results showed that the variable that independence had a negative and significant effect on auditor quality (0.025 < 0.05), while the accountability variable had a positive and significant effect on auditor quality (0.000 < 0.05) and auditor ethics variables had a negative and significant effect on auditor quality (0.49 < 0.05).Keywords: Independence, accountability, auditor ethics, auditor quality